Plant Alkylbenzenes and Terpenoids in the Form of Cyclodextrin Inclusion Complexes as Antibacterial Agents and Levofloxacin Synergists - Igor D. Zlotnikov; Natalya G. Belogurova; Sergey S. Krylov; Marina N. Semenova; Victor V. Semenov; Elena V. Kudryashova (MDPI AG, 2022)
Allylpolyalkoxybenzenes (APABs) and terpenoids from plant essential oils exhibit a range of remarkable biological effects, including analgesic, antibacterial, anti-inflammatory, antioxidant, and others. Synergistic activity with antibiotics of different classes has been reported, with inhibition of P-glycoprotein and impairment of bacterial cell membrane claimed as probable mechanisms. Clearly, a more detailed understanding of APABs' biological activity could help in the development of improved therapeutic options for a range of diseases. However, APABs' poor solubility in water solutions has been a limiting factor for such research. Here, we found that complex formation with β-cyclodextrins (CD) is an efficient way to transform the APABs into a water-soluble form. Using a combination of spectroscopic (FTIR, NMR, UV) methods, we have estimated the binding constants, loading capacity, and the functional groups of both APABs and monoterpenes involved in complex formation with CD: ethylene, aromatic, methoxy and hydroxy groups. In the presence of a molar excess of CD (up to 5 fold) it was possible to achieve the complete dissolution of APABs and terpenoids in an aqueous medium (at 90-98% encapsulation) higher by 10-1000 times. Further, we have demonstrated that CD-APABs, if used in combination with levofloxacin (Lev), can be antagonistic, indifferent, additive, or synergistic, mostly depending on the concentration ratio: at high Lev concentration with the addition of APAB is typically neutral or even antagonistic; while at a Lev concentration below MIC, the addition of CD-APAB is either additive or synergistic (according to FICI criteria). An over three-fold increase in Lev antibacterial activity was observed in combination with eugenol (EG), as per the growth inhibition diameter measurement in agar. Interestingly, a synergistic effect could be observed with both Gram-positive and Gram-negative bacteria. So, obviously, the APAB-CD and terpenoid-CD mechanism of action is not limited to their interaction with the bacterial membrane, which has been shown earlier for CDs. Further research may open new prospects for the development of adjuvants to improve the therapeutic regimens with existing, as well as with new anti-infective drugs.